Heterogeneity Among Poor Ovarian Responders According to Bologna Criteria Results in Diverging Cumulative Live Birth Rates - Romito, Alessia; Bardhi, Erlisa; Errazuriz, Joaquin; Blockeel, Christophe; Santos-Ribeiro, Samuel; Vos, Michel De; Racca, Annalisa; Mackens, Shari; Kelen, Annelore Van Der; Panici, Pierluigi Benedetti; Vaiarelli, Alberto; Tournaye, Herman; et al. (Frontiers in Endocrinology, 2020)
Research question Does reproductive outcome differ among the various subgroups of poor ovarian responders according to the Bologna criteria? Design This was a retrospective, cohort study including poor ovarian responders according to Bologna criteria, undergoing an ICSI cycle from January 2011 until December 2017. Patients were divided into four groups: 1) age ≥ 40 years and abnormal ovarian response test, 2) age ≥ 40 years, abnormal ovarian reserve test and one previous poor response to stimulation 3) age ≥ 40 years and one previous poor response 4) abnormal ovarian reserve test and one previous poor response. Result(s) Overall, 846 cycles in 706 Bologna poor ovarian responders were included: 310 cycles in group 1, 169 in group 2, 52 in group 3 and 315 in group 4. There were significant differences in age, antral follicle count, antimüllerian hormone, cycle cancellation rates and number of retrieved oocytes between the four groups. Live birth and cumulative live birth rate differed significantly between groups and were highest in Group 4 (Live birth rate: 7.4% (1) vs. 4.1% (2) vs. 5.8% (3) vs. 13.4% (4), p =0.001 and Cumulative live birth rate: 8.3% (1) vs. 4.1 % (2) vs. 9.6% (3) vs. 16.8% (4) p<0.001). The multivariate GEE analysis revealed that the number of MIIs and the Bologna criteria pattern were the variables which were significantly associated with cumulative live birth rate. Conclusion(s) Poor ovarian responders represent a heterogeneous population. The young subpopulation has a better clinical prognosis in terms of fresh and cumulative live birth rate.